Contractor Mobilization Process Improvement Using the DMAIC Framework in a Large-Scale Mining Company in Indonesia - Whina Anugraheni Maharani; Liane Okdinawati (Politeknik Siber Cerdika Internasional, 2026)
Background: Contractor mobilization plays a critical role in ensuring workforce readiness and supporting the timely execution of large-scale industrial projects. However, complex administrative requirements, extensive compliance procedures, and coordination among multiple stakeholders often create inefficiencies that affect project performance. Objective: This study analyzes and improves the contractor mobilization process within one of divisions of a large-scale mining company in Indonesia during a major overhaul project. Although the project was planned for 35 calendar days, actual completion required 84 days, indicating substantial deviation from the planned project schedule. Methods: The study employs the Define–Measure–Analyze–Improve–Control (DMAIC) framework using qualitative and quantitative data obtained from interviews, document reviews, and internal performance records. Process performance was assessed using four indicators Mobilization Lead Time (MLT), Mobilization Fulfillment Ratio (MFR), Readiness Compliance (RC), and Delay Frequency (DF), all of which were defined at first use in the text. Results: The findings reveal an average Mobilization Lead Time (MLT) of 57 days, exceeding the 30-working-day service-level target. The overall Mobilization Fulfillment Ratio (MFR) was 82.1% (270 of 329 planned contractors mobilized); however, only 48.6% of contractors were available at project commencement (initial fulfillment rate), while Readiness Compliance (RC) was 27.8% and Delay Frequency (DF) was 40.7%. Conclusion: These improvements are expected to reduce mobilization lead time, enhance workforce readiness, strengthen cross-functional coordination, and improve the overall effectiveness of contractor mobilization management.